Evaluation of genotoxic potential induced by marine cage culture - F. Turan; M. Turgut (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The eutrophication process is increased by anthropogenic or aquaculture facilities in marine ecosystems. DNA damage biomarkers for fish species detect genotoxic parameters for ecological risk assessment. The aim of the present study was to determine genotoxic potential induced by marine cage culture in Iskenderun Bay on gilthead sea bream (Sparus aurata) using Comet assay.  METHODS: This study was conducted at cage and reference stations of Iskenderun Bay, Northeastern Mediterranean in January 2017. The wild and cultured samples of S. aurata and water samples were collected from wild and fish farm.  FINDING: The DNA damages at gill and liver cells of gilthead sea bream in the present study were observed with a higher level of DNA damage in gill cells compared to liver cells, and were determined at the low and minimal scale at the cage and reference stations, respectively. The present study demonstrated that the TP values were recorded at 0.020 and 0.016 mg/L in the cage and reference stations which are at border and below 0.020 mg/L. The DIN values were recorded at 0.097 and 0.075 mg/L in the cage and reference stations, which are at below 0.1 mg/L. The water bodies in the cage and reference stations exhibit Moderate/Mesotrophic water quality The correlations between physical-chemical parameters and DNA damage were shown that DIN, NH4-N, NO3-N and NO2-N in water revealed significant positive correlations with DNA damage levels in gill cells.  CONCLUSION: The present study provides the first data set on genotoxic damage induced by marine cage culture in Iskenderun Bay on gilthead sea bream. The result of this research is an early warning for the marine system and further detailed research is needed to establish the source of the pollution and monitor environmental pollution.